Description of Isoetes afloramientorum, sp. nov. (Isoetaceae), and a second record for Isoetes santacruzensis, two granite outcrop quillworts in Bolivia - Brunton, Daniel F.; de Sousa Pereira, Jovani B. (Phytotaxa, 2020)
A second population of the diploid Isoetes santacruzensis is reported. This extends the range of that newly described endemic of granite outcrop pools by approximately 100 kms southward into central Bolivia from its type location. Another distinct taxon has been detected in the vicinity of the new I. santacruzensis population. The morphology of probably tetraploid I. afloramientorum sp. nov. is described. A cluster of distinct taxa comparable to similar complexes seen in North America, Australia and northern Brazil may be present on Bolivian granite outcrops. There is an urgent need for field investigation of this unique and important habitat to determine the contemporary status and protection requirements of its rare and possibly endangered flora.